Cultural Images of the Ethnic Groups and Ethnic Interrelations in the Balkans - Todorova-Pirgova, Iveta (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1999)
In this paper I work with some cultural representations of ethnic images. I understand ethnic images as mental constructions of ideas, beliefs, opinions, attitudes, and values, created by the members of a given ethnic group and helping them to describe, evaluate and prcsent «our» or «the other» ethnic groups. Ethnic images have different social, psychological, artistic, and other dimensions which need to be studied not only because of their interesting nature as an analytical object, but also because of their significant role as a factor motivating certain behavioural strategies in a situation of interethnic interaction. My observations and conclusions are supported by examples documented over a period of 100 years in order to illustrate the striking constancy of the themes and processes giving rise to ethnic images among some of the ethnic groups living on the Balkan peninsula in the last century and today. Because of the present significance of these problems in the Balkans, I also give examples commenting on current events in the region.